2019
DOI: 10.18203/2349-3291.ijcp20193708
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice of acute diarrheal disease and use of oral rehydration therapy among mothers of under five children

Abstract: Background: Acute diarrhea in children is among the commonest causes of outpatient and inpatient attendance in medical setup. Though enough has been done in imparting knowledge about diarrhea and its management, there is a gap between knowledge and practice in the population. Aim of the study is to assess the mother’s knowledge, attitude and practice about diarrhea in children.Methods: Cross-sectional survey, conducted in the pediatric department of a peripheral hospital in Pune, Maharashtra.Results: Of the 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The level of good knowledge of caregivers in the current study was in line with other previous studies conducted in Nigeria (59.2%) [43], Yemen (51.2%) [44], and India (58.7%) [45]. This could be the result of various initiatives carried out by various governmental and nongovernmental organizations, such as the World Health Organization (WHO), which offered a comprehensive community health seeking behavior through a health task force comprising health extension workers and various healthcare providers.…”
Section: Plos Onesupporting
confidence: 92%
“…The level of good knowledge of caregivers in the current study was in line with other previous studies conducted in Nigeria (59.2%) [43], Yemen (51.2%) [44], and India (58.7%) [45]. This could be the result of various initiatives carried out by various governmental and nongovernmental organizations, such as the World Health Organization (WHO), which offered a comprehensive community health seeking behavior through a health task force comprising health extension workers and various healthcare providers.…”
Section: Plos Onesupporting
confidence: 92%
“…There is very limited study on mothers' attitude towards home-based diarrheal management besides some uses attitude of mother's as a factor that could affect the practice home-based management of diarrhea. Studies suggested that the lack of mothers' attitudes was mainly in uenced by social and cultural beliefs (22)(23)(24)(25). Furthermore, factors like age of the mother, residence, knowledge of HBMD, being single, being less educated, being a housewife were found signi cantly associated with mothers' attitude towards home-based diarrheal management (5,12,13,20,26,27).…”
Section: Introductionmentioning
confidence: 99%